2005
DOI: 10.1271/bbb.69.1562
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Family-9 and Family-22 Carbohydrate-Binding Modules in a Modular β-1,3-1,4-Glucanase/Xylanase Derived fromClostridium stercorariumXyn10B

Abstract: Clostridium stercorarium Xyn10B having hydrolytic activities on xylan and -1,3-1,4-gllucan is a modular enzyme composed of two family-22 carbohydrate-binding modules (CBMs), a family-10 catalytic module of the glycoside hydrolases, a family-9 CBM, and two S-layer homologous modules, consecutively from the N-terminus. We investigated the function of family-9 and family-22 CBMs in a modular enzyme by comparing the enzymatic properties of a truncated enzyme composed of two family-22 CBMs and the catalytic module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Although in general similar patterns of relative activities of these enzymes were observed against oat spelt xylan and pretreated bagasse, but against pretreated biomass the specific activity of XynC-BCB was three fold higher as compared to that of XynC-BC (Table 2) These results show that the binding domain whether attached to the N-or C-terminal of the catalytic domain enhances activity to the same level, whereas the binding domain at both the termini results in further increase in activity. The role of the binding domain belonging to family 22 in facilitating the catalytic domain to bind to the substrate seems to be important for activity as reported previously (Zhao et al, 2005).…”
Section: Xylanase Expression and Activity Yieldssupporting
confidence: 64%
“…Although in general similar patterns of relative activities of these enzymes were observed against oat spelt xylan and pretreated bagasse, but against pretreated biomass the specific activity of XynC-BCB was three fold higher as compared to that of XynC-BC (Table 2) These results show that the binding domain whether attached to the N-or C-terminal of the catalytic domain enhances activity to the same level, whereas the binding domain at both the termini results in further increase in activity. The role of the binding domain belonging to family 22 in facilitating the catalytic domain to bind to the substrate seems to be important for activity as reported previously (Zhao et al, 2005).…”
Section: Xylanase Expression and Activity Yieldssupporting
confidence: 64%
“…From these results, one can conclude that N-or C-terminal accessory domains can make proteins less susceptible to heat, as reported before for other thermophilic or even mesophilic xylanases (Abou-Hachem et al, 2003;Ali et al, 2005;Blanco et al, 1999;Sunna et al, 2000a,b;Zhao et al, 2005). As stated above, the resistance against thermoinactivation of the XTMA catalytic domain is not only the result of a single domain, but is also affected by inter-domain interactions.…”
Section: Effect Of Domains On Thermoactivity and Thermostability Of Rsupporting
confidence: 79%
“…A number of previous results for GH10 xylanases indicated that N-or C-terminal accessory module absence can reduce the thermal stability to the same extent as XynB from Caldicellulosiruptor sp. strain F32 (Table 2) (20,21,44,45). To date, only three crystal structures of GH10 xylanases have been reported together with CBMs, i.e., Cellvibrio japonicus Xyn10C (CjXyn10C; Protein Data Bank entries 1US2 and 1US3) (46), Streptomyces olivaceoviridis Xyn (SoXyn; Protein Data Bank entry 1ISV) (22,47), and Clostridium thermocellum (CtXyn10B; Protein Data Bank entry 2W5F) (6).…”
Section: Discussionmentioning
confidence: 99%